2007
DOI: 10.1002/jmri.20887
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of fibroblastic meningiomas from other benign subtypes using diffusion tensor imaging

Abstract: Purpose: To differentiate fibroblastic meningiomas, usually considered to be of a hard consistency, from other benign subtypes using diffusion tensor imaging (DTI). Materials and Methods:From DTI data sets of 30 patients with benign meningiomas, we calculated diffusion tensors and mean diffusivity (MD) and fractional anisotropy (FA) maps as well as barycentric maps representing the geometrical shape of the tensors. The findings were compared to postoperative histology. The study was approved by the local ethic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
4
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 16 publications
(23 reference statements)
3
40
4
2
Order By: Relevance
“…26 These findings can be explained by the presence of a large amount of collagen in fibroblastic subtypes. 25,33 It has been reported that the structure and orientation of extracellular matrix affect the anisotropy, but not the mean diffusivity 34 ; these results are consistent with ours. On the other hand, in brain metastases, neoplasm cells grow into the brain parenchyma in an expansive, noninfiltrating pattern.…”
Section: Discussionsupporting
confidence: 92%
“…26 These findings can be explained by the presence of a large amount of collagen in fibroblastic subtypes. 25,33 It has been reported that the structure and orientation of extracellular matrix affect the anisotropy, but not the mean diffusivity 34 ; these results are consistent with ours. On the other hand, in brain metastases, neoplasm cells grow into the brain parenchyma in an expansive, noninfiltrating pattern.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies investigated the roles of ADC and FA in subtyping meningiomas, but the results were controversial. 7,8,27 In the present study, we found that angiographic vascularity of meningiomas correlated with FA but not with ADC. Whereas ADC measures the average changes of water diffusivity, FA quantifies the diffusion anisotropy.…”
Section: Discussioncontrasting
confidence: 46%
“…Diffusion tensor imaging, involving 6 or more gradient directions, can also be used to provide information about the tumor consistency and to potentially study the benign and malignant subtypes of meningioma. 28,29 Two patients with benign meningiomas had recurrence of atypical/malignant tumors on follow-up imaging, which showed a change from isointensity to hyperintensity on DW MR imaging and a reduction in the ADC value and NADC ratio below the threshold for higher tumor grade. Although, as a group, the qualitative analysis of the signal intensity on DW MR images was variable and could not be used for distinguishing groups, in these 2 patients, tumor dedifferentiation could be detected visually on presurgical neuroimaging.…”
Section: Discussionmentioning
confidence: 99%